Attempted suicide in a small rural town in the State of Minas Gerais (Brazil): incidence and clinical-demographic profile - Rios Filho, Pedro Paulo Santana; Amorim, Angélica Pereira de; Santos, Gabriela Reis; Silva, Gabriela Souza e; Dadalti, Guilherme Miyakawa; Vargas, Luana Fernanda de Lima; Bueno, Helvécio; Faria, Talitha Araújo (Revista de Medicina, 2016)
The World Health Organization (WHO) published the first Global Report Data for prevention of suicide, in 2014, revealing that more than 800 thousand people give their own lives every year in the world. The survey also says that every 40 seconds a person commits suicide and about 75% of the cases occur in middle-income countries, considered, then, a problem of public health. In the State of Minas Gerais (Central-southernBrazil), according to official estimates (DATASUS) mortalityfrom suicide between the years 2005 and 2009 averaged 5.28per 100,000 inhabitants. The present study is a retrospective,cross-sectional survey to determine suicide-related data frompatients treated at the Paracatu Municipal Hospital MG. Eightyfourmedical files of patients who attempted suicide in 2012were revisited. The results showed a higher incidence of femalesamong those who attempted suicide (mean age 16.2 years), andthe most used methods for suicide attempt was intoxication withdrugs and poisonous substances (predominantly rodenticides).For most patients suicide attempt was a consequence of animpulsive act, fortunately ineffective in the majority of cases.Recurrent cases of attempted suicide were referred to specializedmedical or psychological attention. We conclude that ion viewof the high number of cases of suicide attempt in Paracatu, thecreation of prevention programs about self-extermination andbetter consultation liaison programs increasing the interactionbetween emergency and outpatient facilities are critical needs.